Development of Web Service for Point-of-Sale Application of Kedungudi Sky Park Hill Café - Ari Topan Iqbal Madagaskar; Yulian Firdawati (CV. Media Digital Publikasi Indonesia, 2025)
The rapid development of information technology strengthens the need for efficient system integration in sales management at the Point of Sale (POS) in Sky Park Hill Cafe, Kedungudi. This study explores the application of API (Application Programming Interface) technology to enhance interoperability between the POINT OF SALE (POS) application and other systems. APIs enable more efficient and real-time data exchange between various system components, facilitating accurate transaction recording and timely sales reporting. With the implementation of APIs, it is expected that Sky Park Hill Cafe can improve operational efficiency, increase data transparency, and enhance customer satisfaction through a better shopping experience and more responsive services.